DETERMINAN KEBERHASILAN LELANG EKSEKUSI HAK TANGGUNGAN DI KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG JAKARTA V TAHUN 2008 - 2010 - , Syaipur Rokhman ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research purpose is to analyze factors that effects the success of mortgage execution auction in KPKNL Jakarta V. This research is important because it still has low succeed level which is 14 percent. The object in this auction is real property such as land with or without building. The variables used in this research are location such as distance between real property and closer central business district, accessibility such as road width in front of real property, reserve price that has been set by owner or seller, and turnout or number of bidders in the auction. Data used in this research came from auction minutes held by KPKNL Jakarta V in three years sequentially from 2008 to 2010. Based on these data, about 25 percent were taken for samples or 52 auction minutes wether it sold or not. The samples were processed by using logit model. The result shows that factors effects auction outcome significantly in mortgage auction held by KPKNL Jakarta V are location, reserve price, and turnout or number of bidders. Accessibility effects the auction outcome but not significant.